2007
DOI: 10.1620/tjem.211.31
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Effect of Serotonin on the Voltage-Dependent Ca2+ Current and Subsequently Activated K+ Current in Aplysia Neurons

Abstract: Receptor-induced activation of protein kinase C (PKC) plays an important role in modulation of various types of ionic channels in neurons. For example, PKC causes facilitation or long-lasting activation of certain ionic channels involved in spike firing after the receptor stimulation. We investigated the effect of serotonin (5-HT) on the voltage-dependent Ca 2+ channels in RB and RC neurons of Aplysia ganglia under voltage clamp. An outward current response was induced by voltage change of the cell membrane fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition to direct modulation, ap-GnRH could target the afferents of the recorded neurons to elicit trans-synaptic changes. As the neurocircuits governing movement are complex, it is at present difficult to identify these afferent targets, but the presence of ample sensory–motor connections and interneurons within the central ganglia certainly provides neural substrates for such regulation (Matsumoto et al, 1988; Bley and Tsien, 1990; Kawaski et al, 2007). Overall, ap-GnRH, through both direct and trans-synaptic mechanisms, can generate the diverse responses observed in our intracellular recordings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct modulation, ap-GnRH could target the afferents of the recorded neurons to elicit trans-synaptic changes. As the neurocircuits governing movement are complex, it is at present difficult to identify these afferent targets, but the presence of ample sensory–motor connections and interneurons within the central ganglia certainly provides neural substrates for such regulation (Matsumoto et al, 1988; Bley and Tsien, 1990; Kawaski et al, 2007). Overall, ap-GnRH, through both direct and trans-synaptic mechanisms, can generate the diverse responses observed in our intracellular recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Cd 2+ is a well-known specific blocker of Ca 2+ channels and inhibits Ca 2+ cellular uptake. Electrophysiological investigations in various experimental models have shown that Cd 2+ is commonly used to block voltage-dependent Ca 2+ currents (25) and Ca 2+ -activated K + currents (26)(27)(28)(29). In rat pyramidal neurons (26), 200 µM cadmium was found to markedly reduce the early and late components of Ca 2+ -activated K + current (I K(Ca) ).…”
Section: The Effect Of Mn 2+ On the Outward K + Current Of Leech Retzmentioning
confidence: 99%